The Nature of Relationships among the Components of Pedagogical Content Knowledge of Preservice Science Teachers: 'Ozone layer depletion' as an example - Kaya, Osman N. (Routledge Journals, Taylor & Francis Ltd, 2009)
The purpose of this study was to explore the relationships among the components of preservice science teachers' (PSTs) pedagogical content knowledge (PCK) involving the topic 'ozone layer depletion'. An open-ended survey was first administered to 216 PSTs in their final year at the Faculty of Education to determine their subject matter knowledge of ozone layer depletion. Then, the PSTs were classified as high-ability, average-ability, and low-ability groups according to their scores on the survey. The interviews were carried out with 25 randomly selected PSTs from each of these ability groups in order to determine their pedagogical knowledge and investigate the interrelationships and intra-relationships among the components of the PSTs' PCK for teaching the topic 'ozone layer depletion'. The results showed that there was a significant inter-relationship between the subject matter and pedagogical knowledge of the PSTs. There were also significant intra-relationships among the components of the PSTs' pedagogical knowledge, except for the knowledge of assessment. The results of statistical analyses (multivariate analyses of variance) revealed that there was a significant difference in the degree of the PSTs' pedagogical knowledge by the level of PSTs' subject matter knowledge, These significant results were further supported by evidence from qualitative analyses of the interview data. The implications drawn contribute to the improvement of science teacher education.
Keywords: Models